Lapillus otoliths of the Cathorops spixii (Spix & Agassiz, 1829) and Genidens genidens (Cuvier, 1829) (Actinopterygii - Ariidae) (Acta Scientiarum. Biological Sciences, 2014)
The aim of this study was to analyze the morphology and morphometry of lapillus otoliths of the catfishes Cathorops spixii and Genidens genidens from the coast of Paraná State, Brazil. We used 147 lapillus from C. spixii and 96 from G. genidens, of different size classes. Otoliths were characterized with smooth margins for both species but with different shapes: oblong for C. spixii and oval for G. genidens. The morphological differentiation between the two species is in the anterior region: rounded for C. spixii and pointed for G. genidens. The t-test results for otolith measurements were: length (t value = -2.88; p = 0.0042), height (t value = -6.87; p < 0.000001), anterior angle (t value= 9.84; p = 0.000001) and posterior angle (t value =0.41; p = 0.68). The results show that lapillus otoliths of C. spixii and G. genidens differ in the shape of the anterior region and in the anterior angle, which facilitate the differentiation between the two species in trophic ecology studies on ichthyophagous.